Complexity reduction and opportunities in the design, integration and intensification of biocatalytic processes for metabolite synthesis - Wohlgemuth, Roland; Littlechild, Jennifer (Frontiers in Bioengineering and Biotechnology, 2022)
The biosynthesis of metabolites from available starting materials is becoming an ever important area due to the increasing demands within the life science research area. Access to metabolites is making essential contributions to analytical, diagnostic, therapeutic and different industrial applications. These molecules can be synthesized by the enzymes of biological systems under sustainable process conditions. The facile synthetic access to the metabolite and metabolite-like molecular space is of fundamental importance. The increasing knowledge within molecular biology, enzyme discovery and production together with their biochemical and structural properties offers excellent opportunities for using modular cell-free biocatalytic systems. This reduces the complexity of synthesizing metabolites using biological whole-cell approaches or by classical chemical synthesis. A systems biocatalysis approach can provide a wealth of optimized enzymes for the biosynthesis of already identified and new metabolite molecules.